Potrebe sodobnih družin in državni vidik družinskih centrov v Sloveniji - Boškić, Ružica (Socialno delo, 2012)
In the article, the needs of the families as perceived by the parents, are related to the supply of the family centres as support institutions for assistance to families in meeting their needs. The activities the family centres offer are defined by the state and reflected by the definitions of family centres in the criteria for co-financing of these institutions by public calls. The needs of the modern family have been defined in two researches carried out in Slovenia on the topic in the past two years: The needs of the families for support services (2010) and The needs of the families with the preadolescent children in Slovenia (2010). The analysis shows a significant correlation between the state conceptualization of family centers and family needs. This is especially important for the two most important needs - need for socialising, networking, and the need for occasional child care. However, some of the family centres' activities, such as providing information, could be further strengthened in the future. In addition, we propose that the conceptualization of family centers focuses on the needs of families (not at the same time on the couples who do not yet have children) and that certain substantial requirements are more precisely defined.
Keywords: Family; družina; družinska politika; Family policy; država blaginje; Welfare state; Slovenia; Slovenija